2021
DOI: 10.1101/2021.05.22.445248
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural basis of the interaction between SETD2 methyltransferase and hnRNP L paralogs for governing co-transcriptional splicing

Abstract: The RNA recognition motif (RRM) binds to nucleic acids as well as proteins. More than one such domain is found in the pre-mRNA processing hnRNP proteins. While the mode of RNA recognition by RRMs is known, the molecular basis of their protein interaction remains obscure. Here we describe the mode of interaction between hnRNP L and LL with the methyltransferase SETD2. We demonstrate that for the interaction to occur, a leucine pair within a highly conserved stretch of SETD2 insert their side chains in hydrophob… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…Together our data suggest that in Dnmt3bas OE cells, increased recruitment of hnRNPL at the promoter increases the number of exon inclusion events. Previous studies have shown that the interaction of SETD2 with hnRNPL and elongating RNA Pol II couples transcriptional elongation and alternative splicing (Bhattacharya et al, 2021a; Bhattacharya et al, 2021b; Yuan et al, 2009). We observed no significant change in the deposition of H3K36me3 at the 3’ end of the Dnmt3b gene in Dnmt3bas OE cells compared to the VC cells (Figure S6B), confirming that the activities of SETD2 and hnRNPL are not dependent on their interaction with each other (Yuan et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Together our data suggest that in Dnmt3bas OE cells, increased recruitment of hnRNPL at the promoter increases the number of exon inclusion events. Previous studies have shown that the interaction of SETD2 with hnRNPL and elongating RNA Pol II couples transcriptional elongation and alternative splicing (Bhattacharya et al, 2021a; Bhattacharya et al, 2021b; Yuan et al, 2009). We observed no significant change in the deposition of H3K36me3 at the 3’ end of the Dnmt3b gene in Dnmt3bas OE cells compared to the VC cells (Figure S6B), confirming that the activities of SETD2 and hnRNPL are not dependent on their interaction with each other (Yuan et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown the interaction of SETD2 with hnRNPL and proposed that SETD2 hitchhikes to the elongating Pol II and transports hnRNPL to the splice sites as they emerge during chain elongation(Yuan et al, 2009) (Bhattacharya et al, 2021a; Bhattacharya et al, 2021b). Our study suggests that the recruitment of hnRNPL by Dnmt3bas to the promoter of Dnmt3b facilitates hnRNPL-SETD2 transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we followed a similar template of analysis as previously published to understand the overlap between ARID1B and NEAT1 depletion (Huang et al, 2012;Bhattacharya et al, 2021aBhattacharya et al, , 2021b. For this, using the inclusion-level parameters, we looked for an overlap between the individual up-and downregulated events (Fig EV4B).…”
Section: Neat1 and Arid1b Coregulate Rna-processing Pathwaysmentioning
confidence: 99%